Green asphalt pavement patching material and preparation method thereof

By combining modified milling materials, emulsified asphalt, modified cashew phenol-based epoxy resin, cement and other components, the problems of low bonding strength and non-renewable road repair materials are solved, and high strength, durability and environmental protection are achieved Performance asphalt pavement repair material.

CN119462032AActive Publication Date: 2025-02-18CHINA CONSTRUCTION SIXTH ENGINEERING DIVISION CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411614620.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-18
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

In the prior art, the bonding strength of pavement repair materials is low, especially fragile at low temperatures, and the commonly used toughener is non-renewable and expensive, making it difficult to meet the requirements of modern society for ecological green and sustainable development.

Method used

A combination of modified milling materials, emulsified asphalt, modified cashew phenol-based epoxy resin, cement, mineral powder, water and modified silane coupling agent is used to form high-performance asphalt pavement repair materials through the stirring and curing process.

Benefits of technology

It significantly improves the strength, compactness and durability of the repair material, enhances the bonding ability between milling material and asphalt, and the material has good impact, fatigue and environmental protection properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005131831060000121
    Figure BDA0005131831060000121
  • Figure BDA0005131831060000131
    Figure BDA0005131831060000131
  • Figure BDA0005131831060000132
    Figure BDA0005131831060000132
Patent Text Reader

Abstract

The invention relates to a green asphalt pavement patching material and a preparation method thereof, and the specific formula of the green asphalt pavement patching material comprises the following components by mass: 90-110 parts of a modified milling material; 5-6 parts of emulsified asphalt; 0.6 to 1.2 parts of modified cardanol-based epoxy resin; 10 to 12 parts of cement; 2-3 parts of mineral powder; 3.8 to 4.6 parts of water; and 0.15 to 0.18 part of a modified silane coupling agent. According to the invention, the bonding capacity of the milling material and asphalt is improved, the mechanical strength and water stability of the asphalt mixture are obviously improved, the interface damage caused by load and flowing water scouring is effectively prevented, and the bio-based material is selected, so that the method has the advantages of greenness, environmental protection, economy and recyclability, and has a prospect of large-scale engineering application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of road surface repair material preparation, and in particular to a green asphalt road surface repair material and a preparation method thereof. Background Art

[0002] Most cold patch asphalt repair materials are made of different emulsified asphalt or diluted asphalt and appropriately graded mineral materials. However, ordinary emulsified asphalt has low bonding strength, is brittle at low temperatures, and has a slow strength formation, so the mixture ratio must be modified specifically.

[0003] Epoxy resin emulsified asphalt is a composite material that has been used more and more in recent years. Epoxy resin emulsified asphalt mixture has the advantages of high bonding strength, high shear strength and good high temperature performance. However, due to its high cross-linking density, its curing system has the disadvantages of high brittleness, poor toughness and poor impact resistance, which limits its application in road materials. It is necessary to improve and strengthen the epoxy resin, but the commonly used toughening agents are mostly extracted from petroleum, which are non-renewable and expensive, and it is difficult to meet the requirements of modern society for ecological green, environmental friendliness and sustainable development.

[0004] With the continuous improvement of my country's road network, the roads built in the early stage have gradually entered the stage of major and medium repairs. The milling materials produced by the milling of old roads will not only lead to a waste of resources, but also occupy a large amount of land. The surface of the milling materials is wrapped with the aging asphalt attached to the old road surface. The aromatic compounds in the asphalt gradually decrease from the outside to the inside. The outermost layer of asphalt basically does not contain aromatic compounds, forming an unfavorable structure with a hard and brittle outer layer and a soft inner layer, which is not conducive to the bonding of the milling materials and the new asphalt.

[0005] In order to solve the above problems, there is an urgent need for an asphalt pavement repair material based on milling materials, which is green and environmentally friendly and has excellent performance. Summary of the invention

[0006] The present invention aims to solve the deficiencies of the prior art and provide a green asphalt pavement repair material and a preparation method thereof.

[0007] In order to achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a green asphalt pavement repair material, wherein the specific formula of the green asphalt pavement repair material is composed of the following components in terms of mass fraction ratio:

[0008] 90-110 parts of modified milling material;

[0009] 5-6 parts of emulsified asphalt;

[0010] 0.6-1.2 parts of modified cardanol-based epoxy resin;

[0011] 10-12 parts of cement;

[0012] 2-3 parts of mineral powder;

[0013] 3.8-4.6 parts of water;

[0014] 0.15-0.18 parts of modified silane coupling agent;

[0015] The modified milling material is composed of milling material and corn straw oil, and the mass ratio of the milling material to the corn straw oil is 1:0.01-0.12; and the preparation process is: firstly, the corn straw oil and the milling material are pre-mixed in a stirring pot at 150°C and 40r / min, and then stirred at 150°C and 90r / min for 20min to obtain the modified milling material;

[0016] The modified cardanol-based epoxy resin is composed of octaaniline propyl caged polysilsesquioxane, tetrahydrofuran, cardanol-based epoxy resin, and epoxy curing agent, and the mass ratio of octaaniline propyl caged polysilsesquioxane: tetrahydrofuran: cardanol-based epoxy resin: epoxy curing agent is 0.02-0.025: 0.23-0.25: 1: 1-1.1; the preparation process is: firstly, octaaniline propyl caged polysilsesquioxane is added to tetrahydrofuran and stirred until completely dissolved, then the cardanol-based epoxy resin is added and stirred for 20 minutes, then a rotary evaporator is used for rotary evaporation at 60° C. for 30 minutes, then the epoxy curing agent is added, mechanically stirred for 15 minutes, and then placed in a curing box for curing to obtain the modified cardanol-based epoxy resin;

[0017] The modified silane coupling agent is composed of a silane coupling agent, water, ethanol and acetic acid, and the mass ratio of the silane coupling agent: water: ethanol is 1:1:3. The preparation process is as follows: water and ethanol are mixed to obtain an ethanol aqueous solution, the silane coupling agent is placed in the ethanol aqueous solution for mixing, acetic acid is added to the mixed solution until the pH reaches 4, and the mixed solution is allowed to stand for a period of time to obtain the modified silane coupling agent.

[0018] In particular, the maximum nominal particle size of the modified milling material is 13.2 mm, and the continuous grading particles are uniform.

[0019] In particular, corn stover oil contains acetic acid, hydroxyacetone and acetaldehyde, and is in a viscous liquid state with a density of 0.89 g / cm 3 , pH value is 5.5.

[0020] In particular, the emulsified asphalt is a slow-cracking medium-setting emulsified asphalt with a mixing time of >120s and an initial setting time of 35min.

[0021] Particularly, the cardanol-based epoxy resin is a polyglycidyl ether epoxy phenolic resin derived from cashew nut shell oil, with a viscosity of not less than 28000 CPS and an epoxy equivalent of 550-580.

[0022] Particularly, the cement is a mixture of silicate cement and rapid hardening sulphoaluminate cement, and the mass ratio of silicate cement to rapid hardening sulphoaluminate cement is 8:2; the silicate cement model is P·O 42.5, and the rapid hardening sulphoaluminate cement model is R·SAC42.5.

[0023] Particularly, the mineral powder is limestone mineral powder, the passing rate of the 0.075 mm sieve hole is not less than 80%, and the hydrophilic coefficient is less than 0.8%.

[0024] In particular, the silane coupling agent model is KH-570, the chromatographic purity is 98.7%, and the density is 0.950g / cm 3 , the refractive index is 1.426m / s.

[0025] A method for preparing a green asphalt pavement repair material comprises the following steps:

[0026] S1. Put the weighed cement, mineral powder and modified milling material into a mixing pot and stir at a low speed for 2 minutes to prepare a uniformly mixed dry material mixture A for standby use;

[0027] S2, putting the weighed emulsified asphalt, modified cardanol-based epoxy resin, water, and modified silane coupling agent into a stirring pot and stirring at a low speed for 30 seconds to obtain a mixture B;

[0028] S3. Continue stirring mixture B at a low speed and add the pre-prepared dry material mixture A. After adding the dry material mixture A, continue stirring at a low speed for 30 seconds, then stir at a high speed for 120 seconds, and finally stir at a low speed for 30 seconds to obtain a green asphalt pavement repair material.

[0029] The beneficial effects of the present invention are:

[0030] 1. The present invention achieves uniform compatibility of emulsified asphalt, modified cardanol-based epoxy resin and cement by blending emulsified asphalt, modified cardanol-based epoxy resin and cement. The epoxy resin cured product can form a spatial network structure interlaced with the demulsified asphalt and cement hydration product, thereby improving the overall adhesion and density of the structure. In the development of strength, the hydration reaction of the cementitious material, the curing reaction of the water-based epoxy resin and the emulsified asphalt cementation have achieved coordination and unity, significantly improving the strength of the repair material. At the same time, the epoxy resin can enhance the bonding performance between the cement hydration product and the emulsified asphalt, and the temperature increase and alkaline environment after cement hydration further promote the curing of the epoxy resin.

[0031] 2. Corn straw oil changes the component ratio of aged asphalt on the surface of milling materials and restores the stability of the asphalt colloid structure to a certain extent, thereby restoring the physical and rheological properties of aged asphalt and improving the degree of fusion between milling materials and emulsified asphalt.

[0032] 3. After the milling material is treated with modified silane coupling agent and cement, a stable structure of aged asphalt-silane coupling agent-Ca(OH)2-emulsified asphalt is formed, which makes the bonding ability between the milling material and asphalt stronger, and the mechanical strength and water stability of the asphalt pavement repair material are significantly improved, effectively preventing the interface damage caused by load and dynamic water erosion.

[0033] 4. Cashew phenol-based epoxy resin and corn straw oil are both bio-based materials with the advantages of being green, environmentally friendly, economical and recyclable. They are the best choice for raw materials for large-scale asphalt pavement repairs. DETAILED DESCRIPTION

[0034] The content of the present invention is further described in detail below through several embodiments, and these embodiments are only the implementation technical solutions selected to achieve the purpose of the present invention, rather than being used to limit the protection scope of the present invention. In addition, the range endpoint values ​​and any values ​​given in the present invention are not limited to this precise range or value, and these ranges or values ​​should be values ​​close to these ranges or values.

[0035] The present invention will be further described below in conjunction with embodiments:

[0036] A green asphalt pavement repair material,

[0037] The specific formula of the green asphalt pavement repair material is composed of the following components in terms of mass fraction:

[0038] 90-110 parts of modified milling material;

[0039] 5-6 parts of emulsified asphalt;

[0040] 0.6-1.2 parts of modified cardanol-based epoxy resin;

[0041] 10-12 parts of cement;

[0042] 2-3 parts of mineral powder;

[0043] 3.8-4.6 parts of water;

[0044] 0.15-0.18 parts of modified silane coupling agent.

[0045] The modified milling material consists of milling material and corn straw oil, and the mass ratio of milling material to corn straw oil is 1:0.01-0.12; and the preparation process is: firstly, the corn straw oil and the milling material are pre-mixed in a stirring pot at 150°C and 40r / min, and then stirred at 150°C and 90r / min for 20min to obtain the modified milling material; the modified milling material has a nominal maximum particle size of 13.2mm, and the continuous grading particles are uniform; the corn straw oil contains acetic acid, hydroxyacetone and acetaldehyde, is in a viscous liquid state, and has a density of 0.89g / cm3 , PH value is 5.5. The milling material is taken from the municipal road repair milling material, and the asphalt content is about 8.2%. The use of corn straw oil to modify the milling material has the following advantages:

[0046] Environmental protection and resource recycling: Using corn straw oil as a modifier is a way to convert agricultural waste into valuable industrial raw materials. This method not only reduces the environmental burden of agricultural waste, but also promotes the recycling of resources, which is in line with the principle of sustainable development.

[0047] Improve physical properties: Corn stalk oil contains certain natural resins and wax components, which can improve the physical properties of the planed material, such as increasing its flexibility, crack resistance and adhesion. This means that the modified planed material is more able to adapt to temperature changes, reduce cracks caused by thermal expansion and contraction, and improve the waterproof performance of the material.

[0048] Improve recycling rate: The performance of washed planing material modified with corn straw oil can be significantly improved, which greatly increases the recycling rate of old asphalt materials. This can not only reduce the demand for new materials and production costs, but also reduce the pressure on natural resources.

[0049] Enhanced road performance: The modified washed planed material shows better road performance in practical applications, including but not limited to higher wear resistance, better skid resistance and stronger fatigue resistance. These performance improvements help to extend the service life of the road surface, reduce the frequency of maintenance, and thus save long-term maintenance costs.

[0050] In summary, using corn straw oil to modify washed planed materials can not only effectively improve the physical and road performance of the materials and promote the recycling of resources, but also help protect the environment. It is an economical and environmentally friendly choice.

[0051] The modified cardanol-based epoxy resin is composed of octaaniline propyl caged polysilsesquioxane, tetrahydrofuran, cardanol-based epoxy resin, and epoxy curing agent, and the mass ratio of octaaniline propyl caged polysilsesquioxane: tetrahydrofuran: cardanol-based epoxy resin: epoxy curing agent is 0.02-0.025: 0.23-0.25: 1: 1-1.1; the preparation process is: firstly, octaaniline propyl caged polysilsesquioxane is added to tetrahydrofuran and stirred until completely dissolved, then the cardanol-based epoxy resin is added and stirred for 20 minutes, then a rotary evaporator is used for rotary evaporation at 60° C. for 30 minutes, then the epoxy curing agent is added, mechanically stirred for 15 minutes, and then placed in a curing box for curing to obtain the modified cardanol-based epoxy resin; the cardanol-based epoxy resin is a polyglycidyl ether epoxy phenolic resin derived from cashew nut shell oil, with a viscosity of not less than 28000 CPS and an epoxy equivalent of 550-580.

[0052] Ordinary epoxy resin is a common high-performance polymer with good mechanical strength, chemical corrosion resistance and bonding properties. In asphalt pavement repair materials, it can improve the overall strength and durability of the material. Modified cardanol-based epoxy resin is a new type of resin obtained by introducing cardanol groups into ordinary epoxy resin. This modified resin retains the advantages of ordinary epoxy resin and also has some unique performance advantages. That is:

[0053] Weather resistance: Although ordinary epoxy resin has good chemical corrosion resistance, it may age when exposed to ultraviolet rays and hot and humid environments for a long time. The introduction of cardanol groups in modified cardanol-based epoxy resin significantly improves the weather resistance of the material, making it have a longer life in outdoor environments and not prone to aging.

[0054] Flexibility: Ordinary epoxy resin: Usually brittle and hard, especially under low temperature conditions, it is prone to cracking. Modified cardanol-based epoxy resin: The cardanol group gives the material better flexibility, allowing it to maintain good elasticity and crack resistance at low temperatures, and is suitable for road repairs under different climatic conditions.

[0055] Adhesive properties: Ordinary epoxy resin has good adhesive properties, but its adhesive strength to some substrates is limited. Modified cardanol-based epoxy resin, due to the presence of cardanol groups, has stronger adhesive strength to a variety of substrates (such as metal, concrete, asphalt, etc.), and can better adapt to complex construction environments.

[0056] Chemical corrosion resistance: Ordinary epoxy resin has good chemical corrosion resistance. Modified cardanol-based epoxy resin further enhances chemical corrosion resistance, especially better stability in acid and alkali environments, and is suitable for road repair in special occasions such as chemical plants and ports.

[0057] Environmental protection: Ordinary epoxy resin may cause certain environmental pollution during the production process. Modified cardanol-based epoxy resin, cardanol is extracted from natural plants, has good biodegradability and environmental protection, and is in line with the development trend of green building materials.

[0058] Construction performance: Ordinary epoxy resin has a fast curing speed and needs to be completed in a short time. Modified cardanol-based epoxy resin has a wider construction window, moderate curing speed, easy construction operation, and improved construction flexibility and convenience.

[0059] In summary, modified cardanol-based epoxy resin is superior to ordinary epoxy resin in terms of weather resistance, flexibility, adhesion, chemical corrosion resistance, environmental protection and construction performance. These advantages make modified cardanol-based epoxy resin an ideal choice for high-performance asphalt pavement repair materials, especially for road repair projects that require long-term durability and high reliability.

[0060] The modified silane coupling agent is composed of silane coupling agent, water, ethanol and acetic acid, and the mass ratio of silane coupling agent: water: ethanol is 1:1:3; the preparation process is: water and ethanol are mixed to obtain an ethanol aqueous solution, the silane coupling agent is placed in the ethanol aqueous solution for mixing, acetic acid is added to the mixed solution until the pH reaches 4, and the solution is allowed to stand for a period of time to obtain the modified silane coupling agent. The silane coupling agent model is KH-570, the chromatographic purity is 98.7%, and the density is 0.950g / cm 3 , the refractive index is 1.426m / s.

[0061] In asphalt repair materials, the use of modified silane coupling agents has many advantages over ordinary silane coupling agents. Through specific chemical modification, modified silane coupling agents can better adapt to the characteristics of asphalt materials and construction environments, thereby achieving significant improvements in multiple performance indicators. That is:

[0062] Enhanced interfacial bonding: Ordinary silane coupling agents can improve the interfacial bonding between inorganic fillers and organic polymer matrices, but the effect is limited. Modified silane coupling agents, through chemical modification, can more effectively form stable chemical bonds between inorganic fillers and organic polymers, significantly enhance interfacial bonding, and improve the overall strength and toughness of the material.

[0063] Improve weather resistance: Ordinary silane coupling agents may age when exposed to ultraviolet rays and hot and humid environments for a long time. Modified silane coupling agents have better weather resistance and can effectively resist the influence of ultraviolet rays and hot and humid environments, extending the service life of the material.

[0064] Improved flexibility: Ordinary silane coupling agents may make the material brittle and prone to cracking under low temperature conditions. Modified silane coupling agents can give the material better flexibility, allowing it to maintain good elasticity and crack resistance at low temperatures, and are suitable for road repairs under different climatic conditions.

[0065] Enhanced bonding performance: Although ordinary silane coupling agents can improve the bonding performance of materials, their bonding strength to certain substrates is limited. Modified silane coupling agents have stronger bonding strength to a variety of substrates (such as metal, concrete, asphalt, etc.) and can better adapt to complex construction environments.

[0066] Improve chemical corrosion resistance: Ordinary silane coupling agents already have good chemical corrosion resistance. Modified silane coupling agents further enhance chemical corrosion resistance, especially better stability in acid and alkali environments, and are suitable for road repair in special occasions such as chemical plants and ports.

[0067] Improve construction performance: Ordinary silane coupling agents may have uneven dispersion during construction, affecting construction quality. Modified silane coupling agents have better dispersibility and compatibility, and can be more evenly distributed in the material during construction, improving construction convenience and quality.

[0068] Improve fatigue resistance: Ordinary silane coupling agents may suffer fatigue damage under repeated loads. Modified silane coupling agents can significantly improve the material's fatigue resistance, reduce damage caused by repeated loads, and extend the service life of the road surface.

[0069] Environmental protection: Ordinary silane coupling agents may cause certain environmental pollution during production and use. Modified silane coupling agents usually have better biodegradability and environmental protection, which is in line with the development trend of green building materials.

[0070] In summary, modified silane coupling agents have many advantages in asphalt repair materials, such as enhanced interface bonding, improved weather resistance, improved flexibility, enhanced bonding performance, improved chemical corrosion resistance, improved construction performance, improved fatigue resistance and environmental protection. These advantages make modified silane coupling agents an ideal choice for high-performance asphalt repair materials, especially for road repair projects that require long-term durability and high reliability.

[0071] Emulsified asphalt is a slow-cracking medium-setting emulsified asphalt, with a mixing time of >120s and an initial setting time of 35min. Among asphalt pavement repair materials, the use of slow-cracking medium-setting emulsified asphalt has many advantages. That is:

[0072] Extend construction time: Slow cracking means that the emulsified asphalt will not demulsify quickly after spraying or mixing, which provides construction workers with a longer operating time and facilitates uniform paving and compaction. Medium setting, moderate setting time, ensures that the emulsified asphalt can form a stable structure within a reasonable time after the construction is completed, avoiding premature or late solidification.

[0073] Improve construction quality: Uniform distribution and slow cracking characteristics enable emulsified asphalt to be more evenly distributed when mixed with aggregates, improving the uniformity and density of the mixture. Better adhesion, slow-cracking medium-setting emulsified asphalt can better penetrate into the aggregate surface during the demulsification process, enhance the adhesion between aggregates, and improve the stability of the overall structure.

[0074] Adapt to different climatic conditions: Temperature adaptability: Slow-cracking medium-setting emulsified asphalt can maintain good fluidity at lower temperatures and is suitable for construction in different seasons and temperature conditions. Humidity adaptability: In a humid environment, the slow-cracking property can prevent the emulsified asphalt from breaking too quickly, ensuring the construction quality and effect.

[0075] Reduce early damage: Initial strength, slow-cracking medium-setting emulsified asphalt has high initial strength after construction, which can reduce early damage to the newly repaired road surface caused by vehicles passing through. Anti-cracking performance, slow-cracking characteristics allow emulsified asphalt to gradually form a stable structure during the solidification process, reducing cracks caused by rapid solidification.

[0076] Economical: High material utilization rate and slow cracking characteristics ensure full utilization of emulsified asphalt during construction, reducing waste. Low construction cost, long construction time and good construction performance reduce construction difficulty and the possibility of rework, thereby reducing overall construction costs.

[0077] Environmental protection: Low volatility, slow-crack medium-setting emulsified asphalt has low volatility during construction, reducing the emission of harmful substances and being more environmentally friendly. Recyclability: The stable structure formed by emulsified asphalt after construction is conducive to the recycling and reuse of materials, meeting the requirements of sustainable development.

[0078] In summary, the application of slow-cracking medium-setting emulsified asphalt in asphalt pavement repair materials can not only prolong the construction time and improve the construction quality, but also adapt to different climatic conditions, reduce early damage, and have good economy and environmental protection. These advantages make slow-cracking medium-setting emulsified asphalt the preferred material in pavement repair projects.

[0079] The cement is a mixture of silicate cement and rapid hardening sulphoaluminate cement, and the mass ratio of silicate cement to rapid hardening sulphoaluminate cement is 8:2; the silicate cement model is P·O 42.5, and the rapid hardening sulphoaluminate cement model is R·SAC42.5. Mixing silicate cement and rapid hardening sulphoaluminate cement can bring many advantages in asphalt pavement repair materials, namely:

[0080] Fast hardening: Rapid hardening sulphoaluminate cement has the characteristics of fast hardening and can reach high early strength in a shorter time. This allows the repair material to be put into use quickly after construction, reducing traffic interruption time. Although silicate cement hardens relatively slowly, its late strength is high and can provide long-term stability. Mixing these two cements can balance early strength and late strength, achieving the dual advantages of fast hardening and long-term stability.

[0081] Improve early strength: Rapid hardening sulphoaluminate cement provides higher strength in the early stages, helping to reduce the risk of deformation and damage to the repair material after construction. Portland cement continues to provide strength growth in the later stages, ensuring the long-term performance of the repair material.

[0082] Enhanced durability: Portland cement has good durability and corrosion resistance, and can resist chemical erosion and environmental factors. Rapid hardening sulphoaluminate cement, although high in early strength, has relatively low durability. Mixed use can make up for this deficiency and improve overall durability.

[0083] Improve working performance: Rapid hardening sulphoaluminate cement has good fluidity and plasticity, which is convenient for construction operation. Portland cement has good adhesion and stability, which helps to improve the overall performance of the mixture. Mixing can optimize working performance and make construction more convenient and efficient.

[0084] Adapt to different climatic conditions: Rapid hardening sulphoaluminate cement can harden quickly even at low temperatures and is suitable for winter construction. Portland cement has good stability at high temperatures and is suitable for summer construction. Mixed use can adapt to construction needs under different climatic conditions.

[0085] Reduce shrinkage cracks: Rapid hardening sulphoaluminate cement has a lower shrinkage rate and can reduce cracks caused by shrinkage. Although silicate cement has a higher shrinkage rate, its later strength is high and can provide better overall stability. Mixing can reduce shrinkage cracks and improve the crack resistance of the repair material.

[0086] Economical: Cost-effective, although the price of rapid hardening sulphoaluminate cement is higher, the amount used is less; the price of silicate cement is relatively low, and the amount used is larger. Mixed use can balance the cost and achieve dual optimization of economy and performance.

[0087] In summary, the mixed use of silicate cement and fast-hardening sulphoaluminate cement can achieve many advantages in asphalt pavement repair materials, such as rapid hardening, improved early strength, enhanced durability, improved working performance, adaptation to different climatic conditions, and reduced shrinkage cracks. This mixed cement not only improves construction efficiency and repair quality, but also has good economy and practicality, and is an ideal choice for asphalt pavement repair materials.

[0088] The mineral powder is limestone powder, the passing rate of 0.075mm sieve is not less than 80%, and the hydrophilic coefficient is less than 0.8%. The selection of this mineral powder has the following advantages:

[0089] Fineness advantage: The passing rate of 0.075mm sieve is not less than 80%, which means that the mineral powder particles are very fine. The mineral powder with high fineness can better fill the gaps in the mixture and improve the density and stability of the mixture. Fine particles can also increase the contact area between asphalt and aggregate, improve the bonding force, and thus enhance the overall mechanical properties.

[0090] Low hydrophilic coefficient: The hydrophilic coefficient is less than 0.8%. Low hydrophilic coefficient means that the mineral powder has a weaker ability to adsorb water, which has the following benefits: Reduce the impact of moisture. Mineral powder with a low hydrophilic coefficient is not easy to absorb water during construction, reducing the negative impact of moisture on the performance of the mixture, especially when constructing in a humid environment, it can maintain the stability and workability of the mixture. Improve durability. Mineral powder with a low hydrophilic coefficient can reduce the penetration of water inside the material, reduce the damage to the road surface caused by freeze-thaw cycles, and improve the durability of the road surface. Enhance adhesion. Mineral powder with a low hydrophilic coefficient is easier to combine with asphalt to form a more stable asphalt mortar, which enhances the cohesion and adhesion of the asphalt mixture.

[0091] Improve the performance of the mixture: Improve stability. Mineral powder with high fineness and low hydrophilicity can improve the high temperature stability and low temperature crack resistance of the asphalt mixture, and reduce the occurrence of rutting and cracks. Improve rheological properties. Fine-grained mineral powder can improve the rheological properties of the mixture, making it easier to spread and compact during construction, improving construction quality. Enhance anti-stripping performance. Mineral powder with low hydrophilicity can reduce the erosion of water on the asphalt film, improve the bonding force between asphalt and aggregate, reduce the spalling of the asphalt film, and improve the anti-stripping performance of the road surface.

[0092] Environmental protection and economy: Reduce material waste. Mineral powder with high fineness and low hydrophilicity coefficient can be better utilized, reduce material waste and construction costs. Extend service life. High-quality mineral powder can improve the overall performance of the road surface, extend the service life of the road surface, reduce the frequency of maintenance and renovation, and has good economy.

[0093] In summary, the use of limestone powder that meets specific technical requirements (pass rate of 0.075mm sieve hole is not less than 80%, hydrophilic coefficient is less than 0.8%) in asphalt pavement repair materials can significantly improve the density, stability, durability and anti-stripping performance of the mixture. These advantages not only improve the construction quality, but also extend the service life of the pavement, and have good economic and environmental protection.

[0094] A method for preparing a green asphalt pavement repair material comprises the following steps:

[0095] S1. Put the weighed cement, mineral powder and modified milling material into a mixing pot and stir at a low speed for 2 minutes to prepare a uniformly mixed dry material mixture A for standby use;

[0096] S2, putting the weighed emulsified asphalt, modified cardanol-based epoxy resin, water, and modified silane coupling agent into a stirring pot and stirring at a low speed for 30 seconds to obtain a mixture B;

[0097] S3. Continue stirring mixture B at a low speed and add the pre-prepared dry material mixture A. After adding the dry material mixture A, continue stirring at a low speed for 30 seconds, then stir at a high speed for 120 seconds, and finally stir at a low speed for 30 seconds to obtain a green asphalt pavement repair material.

[0098] In the above S2, the emulsified asphalt provides good adhesion and plasticity, ensuring that the material is easy to spread and compact during the construction process. The modified cardanol-based epoxy resin provides excellent mechanical strength, weather resistance, chemical corrosion resistance and flexibility. Water acts as a solvent to help the emulsified asphalt and other components to be evenly dispersed. The modified silane coupling agent enhances the interfacial bonding between the inorganic filler and the organic polymer, thereby improving the strength and toughness of the overall material. After mixing the mixture B and the dry material mixture A, a high-performance asphalt repair material can be formed. This material has significant advantages in early strength, rapid hardening, durability, crack resistance, flexibility, bonding performance, construction performance, fatigue resistance and environmental protection, and is particularly suitable for road repair projects that require long-term durability and high reliability.

[0099] Example 1

[0100] A green asphalt pavement repair material, the specific formula of the green asphalt pavement repair material, is composed of the following components in mass fraction: 100 parts of modified milling material, 5 parts of emulsified asphalt, 0.6 parts of modified cardanol-based epoxy resin, 10 parts of cement, 2 parts of mineral powder, 3.8 parts of water, and 0.16 parts of modified silane coupling agent.

[0101] A method for preparing a green asphalt pavement repair material comprises the following steps:

[0102] S1. Put the weighed cement, mineral powder and modified milling material into a mixing pot and stir at a low speed for 2 minutes to prepare a uniformly mixed dry material mixture A for standby use;

[0103] S2, putting the weighed emulsified asphalt, modified cardanol-based epoxy resin, water, and modified silane coupling agent into a stirring pot and stirring at a low speed for 30 seconds to obtain a mixture B;

[0104] S3. Continue stirring mixture B at a low speed and add the pre-prepared dry material mixture A. After adding the dry material mixture A, continue stirring at a low speed for 30 seconds, then stir at a high speed for 120 seconds, and finally stir at a low speed for 30 seconds to obtain a green asphalt pavement repair material.

[0105] Example 2

[0106] A green asphalt pavement repair material, the specific formula of the green asphalt pavement repair material, is composed of the following components in mass fraction: 100 parts of modified milling material, 5.5 parts of emulsified asphalt, 0.9 parts of modified cardanol-based epoxy resin, 11 parts of cement, 2.5 parts of mineral powder, 4.2 parts of water, and 0.16 parts of modified silane coupling agent.

[0107] A method for preparing a green asphalt pavement repair material comprises the following steps:

[0108] S1. Put the weighed cement, mineral powder and modified milling material into a mixing pot and stir at a low speed for 2 minutes to prepare a uniformly mixed dry material mixture A for standby use;

[0109] S2, putting the weighed emulsified asphalt, modified cardanol-based epoxy resin, water, and modified silane coupling agent into a stirring pot and stirring at a low speed for 30 seconds to obtain a mixture B;

[0110] S3. Continue stirring mixture B at a low speed and add the pre-prepared dry material mixture A. After adding the dry material mixture A, continue stirring at a low speed for 30 seconds, then stir at a high speed for 120 seconds, and finally stir at a low speed for 30 seconds to obtain a green asphalt pavement repair material.

[0111] Example 3

[0112] A green asphalt pavement repair material, the specific formula of the green asphalt pavement repair material, is composed of the following components in mass fraction: 100 parts of modified milling material, 6 parts of emulsified asphalt, 1.2 parts of modified cardanol-based epoxy resin, 12 parts of cement, 3 parts of mineral powder, 4.6 parts of water, and 0.18 parts of modified silane coupling agent.

[0113] A method for preparing a green asphalt pavement repair material comprises the following steps:

[0114] S1. Put the weighed cement, mineral powder and modified milling material into a mixing pot and stir at a low speed for 2 minutes to prepare a uniformly mixed dry material mixture A for standby use;

[0115] S2, putting the weighed emulsified asphalt, modified cardanol-based epoxy resin, water, and modified silane coupling agent into a stirring pot and stirring at a low speed for 30 seconds to obtain a mixture B;

[0116] S3. Continue stirring mixture B at a low speed and add the pre-prepared dry material mixture A. After adding the dry material mixture A, continue stirring at a low speed for 30 seconds, then stir at a high speed for 120 seconds, and finally stir at a low speed for 30 seconds to obtain a green asphalt pavement repair material.

[0117] Comparative Example 1

[0118] A green asphalt pavement repair material, the specific formula of the green asphalt pavement repair material, is composed of the following components in mass fraction: 100 parts of milling material, 6 parts of emulsified asphalt, 1.2 parts of modified cardanol-based epoxy resin, 12 parts of cement, 3 parts of mineral powder, 4.6 parts of water, and 0.18 parts of modified silane coupling agent.

[0119] A method for preparing a green asphalt pavement repair material comprises the following steps:

[0120] S1. Put the weighed cement, mineral powder and milling material into a mixing pot and stir at a low speed for 2 minutes to prepare a uniformly mixed dry material mixture A for standby use;

[0121] S2, putting the weighed emulsified asphalt, modified cardanol-based epoxy resin, water, and modified silane coupling agent into a stirring pot and stirring at a low speed for 30 seconds to obtain a mixture B;

[0122] S3. Continue stirring mixture B at a low speed and add the pre-prepared dry material mixture A. After adding the dry material mixture A, continue stirring at a low speed for 30 seconds, then stir at a high speed for 120 seconds, and finally stir at a low speed for 30 seconds to obtain a green asphalt pavement repair material.

[0123] Comparative Example 2

[0124] A green asphalt pavement repair material, the specific formula of the green asphalt pavement repair material, is composed of the following components in mass fraction: 100 parts of modified milling material, 6 parts of emulsified asphalt, 12 parts of cement, 3 parts of mineral powder, 4.6 parts of water, and 0.18 parts of modified silane coupling agent.

[0125] A method for preparing a green asphalt pavement repair material comprises the following steps:

[0126] S1. Put the weighed cement, mineral powder and modified milling material into a mixing pot and stir at a low speed for 2 minutes to prepare a uniformly mixed dry material mixture A for standby use;

[0127] S2. Put the weighed emulsified asphalt, water and modified silane coupling agent into a stirring pot and stir at a low speed for 30 seconds to obtain a mixture B;

[0128] S3. Continue stirring mixture B at a low speed and add the pre-prepared dry material mixture A. After adding the dry material mixture A, continue stirring at a low speed for 30 seconds, then stir at a high speed for 120 seconds, and finally stir at a low speed for 30 seconds to obtain a green asphalt pavement repair material.

[0129] Comparative Example 3

[0130] A green asphalt pavement repair material, the specific formula of the green asphalt pavement repair material, is composed of the following components in mass fraction: 100 parts of modified milling material, 6 parts of emulsified asphalt, 1.2 parts of modified cardanol-based epoxy resin, 3 parts of mineral powder, 4.6 parts of water, and 0.18 parts of modified silane coupling agent.

[0131] A method for preparing a green asphalt pavement repair material comprises the following steps:

[0132] S1. Put the weighed mineral powder and modified milling material into a stirring pot and stir at a low speed for 2 minutes to prepare a uniformly mixed dry material mixture A for standby use;

[0133] S2, putting the weighed emulsified asphalt, modified cardanol-based epoxy resin, water, and modified silane coupling agent into a stirring pot and stirring at a low speed for 30 seconds to obtain a mixture B;

[0134] S3. Continue stirring mixture B at a low speed and add the pre-prepared dry material mixture A. After adding the dry material mixture A, continue stirring at a low speed for 30 seconds, then stir at a high speed for 120 seconds, and finally stir at a low speed for 30 seconds to obtain a green asphalt pavement repair material.

[0135] Comparative Example 4

[0136] A green asphalt pavement repair material, the specific formula of the green asphalt pavement repair material, is composed of the following components in mass fraction: 100 parts of modified milling material, 6 parts of emulsified asphalt, 1.2 parts of modified cardanol-based epoxy resin, 12 parts of cement, 3 parts of mineral powder, and 4.6 parts of water.

[0137] A method for preparing a green asphalt pavement repair material comprises the following steps:

[0138] S1. Put the weighed cement, mineral powder and modified milling material into a mixing pot and stir at a low speed for 2 minutes to prepare a uniformly mixed dry material mixture A for standby use;

[0139] S2, put the weighed emulsified asphalt, modified cardanol-based epoxy resin and water into a stirring pot and stir at a low speed for 30 seconds to obtain a mixture B;

[0140] S3. Continue stirring mixture B at a low speed and add the pre-prepared dry material mixture A. After adding the dry material mixture A, continue stirring at a low speed for 30 seconds, then stir at a high speed for 120 seconds, and finally stir at a low speed for 30 seconds to obtain a green asphalt pavement repair material.

[0141] The amounts of the components of the green asphalt pavement repair materials in Examples 1-3 and Comparative Examples 1-4 are shown in Table 1.

[0142] Table 1 Amount of each component of green asphalt pavement repair material in Examples 1-3 and Comparative Examples 1-4

[0143]

[0144]

[0145] According to the standard asphalt pavement pothole cold patch finished material (JT / T 972-2015), the test procedure for asphalt and asphalt mixture in highway engineering (JTG E20-2011), and the highway asphalt pavement construction specification (JTG F40-2004), the workability grade, damage rate, initial Marshall stability, forming Marshall stability and Marshall residual stability of the green asphalt pavement repair materials in Examples 1-3 and Comparative Examples 1-4 were tested respectively, and the test results are shown in Table 2.

[0146] Table 2 Performance of green asphalt pavement repair materials in Examples 1-3 and Comparative Examples 1-4

[0147]

[0148] By comparing the performance results between Examples 1-3 and Comparative Examples 1-4 in Table 2, it can be found that the repair material prepared by mixing the modified cardanol-based epoxy resin, cement and modified silane coupling agent material is generally superior to the asphalt repair material prepared by using them alone or in combination. In particular, when the modified silane coupling agent material is added to the epoxy resin, cement and asphalt mixture, a stable structure of aged asphalt-silane coupling agent-Ca(OH)2-emulsified asphalt is formed, which strengthens the mutual bonding between the components of the newly prepared mixture and strengthens the connection with the aged asphalt at the interface of the existing road surface, which is of great significance for improving the effect of road pothole repair.

[0149] By comparing Example 3 and Comparative Example 1, it can be found that the modified milling material can be better integrated with the emulsified asphalt binder. Compared with the unmodified milling material, the modified milling material effectively improves the cohesion, initial strength, molding strength and water stability of the repair material. Corn straw oil changes the component ratio of aged asphalt on the surface of the milling material and restores the stability of the asphalt colloid structure to a certain extent, thereby restoring the physical and rheological properties of the aged asphalt and improving the degree of integration between the milling material and the emulsified asphalt. After the milling material is treated with modified silane coupling agent and cement, a stable structure of aged asphalt-silane coupling agent-Ca(OH)2-emulsified asphalt is formed, which makes the milling material and asphalt more capable of bonding, and the mechanical strength and water stability of the asphalt mixture are significantly improved, which effectively prevents the interface damage caused by load and dynamic water scouring.

[0150] Comparing Example 3 and Comparative Example 2, it can be found that the damage rate of the asphalt pavement repair material obtained in Comparative Example 2 is greatly improved, and the cohesive force of the mixture decreases, indicating that modified cardanol-based epoxy resin has a better bonding effect. By the blending of emulsified asphalt, modified cardanol-based epoxy resin, and cement, the uniform compatibility of emulsified asphalt, modified cardanol-based epoxy resin, and cement is achieved, and the epoxy resin cured product can form a spatial network structure interlaced with the asphalt and cement hydration products after demulsification, thereby improving the overall cohesiveness and compactness of the structure. In the strength development, the cementitious material hydration reaction, the water-based epoxy resin curing reaction, and the emulsified asphalt cementation have reached coordination and unity, significantly improving the strength of the repair material. At the same time, epoxy resin can enhance the bonding performance between cement hydration products and emulsified asphalt, and the temperature rise and alkaline environment after cement hydration further promote the curing of epoxy resin. Cardanol-based epoxy resin and corn stalk oil are both bio-based materials, with the advantages of green environmental protection, economic savings, and recyclability, and are the only choice for large-scale asphalt pavement repair raw materials.

[0151] By comparing Example 3 and Comparative Example 3, it can be found that cement significantly affects the initial strength of the asphalt pavement repair material, and the early strength develops quickly, which is more conducive to the early opening of road traffic.

[0152] By comparing Example 3 and Comparative Example 4, it can be found that the damage rate of the asphalt pavement repair material obtained after adding the modified silane coupling agent is reduced: This shows that after adding the modified silane coupling agent, the durability and crack resistance of the repair material are improved. The silane coupling agent can enhance the interfacial bonding between the inorganic filler and the organic polymer matrix, thereby improving the overall strength and toughness of the material and reducing the damage caused by external stress. The initial Marshall stability is improved: Marshall stability is an important indicator to measure the ability of asphalt mixture to resist rutting deformation. The improvement of initial Marshall stability means that the newly paved or repaired pavement has better bearing capacity and rutting resistance in the early stage, which is very important for ensuring the initial use quality of the road. The molding Marshall stability is improved: This improvement in performance shows that the modified silane coupling agent helps to improve the stability of the asphalt mixture during the molding process, that is, it can still maintain a high structural strength after compaction and other treatments, which is very critical to ensure the long-term performance of the pavement. Improved Marshall residual stability: Marshall residual stability reflects the stability of asphalt mixture after aging under certain conditions (such as high temperature, ultraviolet radiation). The increase in this value indicates that the addition of modified silane coupling agents can effectively delay the aging process of the material and extend the service life of the pavement. In summary, by adding modified silane coupling agents to asphalt pavement repair materials, not only can the damage rate be reduced, but also significant improvements can be achieved in multiple key performance indicators, thereby improving the quality and efficiency of pavement repairs, extending the service life of the road, and potentially reducing future maintenance costs.

[0153] The present invention improves the bonding ability between milling material and asphalt, significantly improves the mechanical strength and water stability of asphalt mixture, effectively prevents interface damage caused by load and dynamic water scouring, and uses bio-based materials, which has the advantages of being green, environmentally friendly, economical and recyclable, and has the prospect of large-scale engineering application.

[0154] The above is an exemplary description of the present invention. Obviously, the specific implementation of the present invention is not limited to the above-mentioned method. As long as various improvements are made using the method concept and technical solution of the present invention, or they are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.

Claims

1. A green asphalt pavement repair material, characterized by: The specific formula of the green asphalt pavement repair material is composed of the following components in terms of mass fraction: 90-110 parts of modified milling material; 5-6 parts of emulsified asphalt; 0.6-1.2 parts of modified cardanol-based epoxy resin; 10-12 parts of cement; 2-3 parts of mineral powder; 3.8-4.6 parts of water; 0.15-0.18 parts of modified silane coupling agent; The modified milling material is composed of milling material and corn straw oil, and the mass ratio of the milling material to the corn straw oil is 1:0.01-0.12; and the preparation process is: firstly, the corn straw oil and the milling material are pre-mixed in a stirring pot at 150°C and 40r / min, and then stirred at 150°C and 90r / min for 20min to obtain the modified milling material; The modified cardanol-based epoxy resin is composed of octaaniline propyl caged polysilsesquioxane, tetrahydrofuran, cardanol-based epoxy resin, and epoxy curing agent, and the mass ratio of octaaniline propyl caged polysilsesquioxane: tetrahydrofuran: cardanol-based epoxy resin: epoxy curing agent is 0.02-0.025: 0.23-0.25: 1: 1-1.1; the preparation process is: firstly, octaaniline propyl caged polysilsesquioxane is added to tetrahydrofuran and stirred until completely dissolved, then the cardanol-based epoxy resin is added and stirred for 20 minutes, then a rotary evaporator is used for rotary evaporation at 60° C. for 30 minutes, then the epoxy curing agent is added, mechanically stirred for 15 minutes, and then placed in a curing box for curing to obtain the modified cardanol-based epoxy resin; The modified silane coupling agent is composed of a silane coupling agent, water, ethanol and acetic acid, and the mass ratio of the silane coupling agent: water: ethanol is 1:1:

3. The preparation process is as follows: water and ethanol are mixed to obtain an ethanol aqueous solution, the silane coupling agent is placed in the ethanol aqueous solution for mixing, acetic acid is added to the mixed solution until the pH reaches 4, and the mixed solution is allowed to stand for a period of time to obtain the modified silane coupling agent.

2. A green asphalt pavement repair material according to claim 1, characterized in that: The maximum nominal particle size of the modified milling material is 13.2 mm, and the continuous grading particles are uniform.

3. A green asphalt pavement repair material according to claim 1, characterized in that: Corn straw oil contains acetic acid, hydroxyacetone and acetaldehyde. It is a viscous liquid with a density of 0.89 g / cm 3 , pH value is 5.

5.

4. A green asphalt pavement repair material according to claim 1, characterized in that: Emulsified asphalt is a slow-cracking, medium-setting type of emulsified asphalt with a mixing time of >120s and an initial setting time of 35min.

5. The green asphalt pavement repair material according to claim 1, characterized in that: The cardanol-based epoxy resin is a polyglycidyl ether epoxy phenolic resin derived from cashew nut shell oil, with a viscosity of not less than 28000 CPS and an epoxy equivalent of 550 to 580.

6. The green asphalt pavement repair material according to claim 1, characterized in that: The cement is a mixture of silicate cement and rapid hardening sulphoaluminate cement, and the mass ratio of silicate cement to rapid hardening sulphoaluminate cement is 8:2; the silicate cement model is P·O 42.5, and the rapid hardening sulphoaluminate cement model is R·SAC42.

5.

7. The green asphalt pavement repair material according to claim 1, characterized in that: The mineral powder is limestone mineral powder, the passing rate of the 0.075mm sieve hole is not less than 80%, and the hydrophilic coefficient is less than 0.8%.

8. The green asphalt pavement repair material according to claim 1, characterized in that: The silane coupling agent model is KH-570, the chromatographic purity is 98.7%, and the density is 0.950g / cm 3 , the refractive index is 1.426m / s.

9. A method for preparing the green asphalt pavement repair material according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Put the weighed cement, mineral powder and modified milling material into a mixing pot and stir at a low speed for 2 minutes to prepare a uniformly mixed dry material mixture A for standby use; S2, putting the weighed emulsified asphalt, modified cardanol-based epoxy resin, water, and modified silane coupling agent into a stirring pot and stirring at a low speed for 30 seconds to obtain a mixture B; S3. Continue stirring mixture B at a low speed and add the pre-prepared dry material mixture A. After adding the dry material mixture A, continue stirring at a low speed for 30 seconds, then stir at a high speed for 120 seconds, and finally stir at a low speed for 30 seconds to obtain a green asphalt pavement repair material.

Citation Information

Patent Citations

  • Plant-mixed thermally-modified asphalt regenerated mix and preparation method thereof

    CN102786257A

  • Pavement quick-repair asphalt mixture, and preparation method and application method thereof

    CN105645850A

  • Cold-regeneration quick repairing material and preparation method thereof

    CN106587821A

  • Low-viscosity perfusion adhesive for repairing concrete crack and preparation method thereof

    CN108384497A

  • Method for improving adhesion of asphalt mixture based on silane coupling agent hydrolyzed powder

    CN114316362A